2019
DOI: 10.2478/jim-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Shear Stress after Implantation of Bioresorbable Scaffolds – a Modern Interdisciplinary Concept at the Border between Interventional Cardiology and Cardiac Imaging

Abstract: Bioresorbable scaffolds/stents offer new and exciting perspectives in the treatment of patients with acute coronary syndromes, especially after the recent development of invasive imaging techniques, such as optical coherence tomography, which allow complete assessment of vascu-lar segments. A particular advantage of bioresorbable scaffolds is that once the biosorption of the scaffold is complete, the vascular segment regains its normal physiological functions, thus eliminating the risk of late complications. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Location of coronary lesions may also play a significant role on the clinical outcomes, since it has been demonstrated that an increased shear stress at the level of coronary bifurcations may accelerate the plaque vulnerabilisation process, [ 25 ] while location in the proximal left anterior descendant artery is association with an increased risk of cardiac arrest. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Location of coronary lesions may also play a significant role on the clinical outcomes, since it has been demonstrated that an increased shear stress at the level of coronary bifurcations may accelerate the plaque vulnerabilisation process, [ 25 ] while location in the proximal left anterior descendant artery is association with an increased risk of cardiac arrest. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%